2021
DOI: 10.1016/s2468-2667(21)00228-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trend and attributable risk factors of stroke burden in China, 1990–2019: an analysis for the Global Burden of Disease Study 2019

Abstract: Background Understanding the temporal trend of the disease burden of stroke and its attributable risk factors in China, especially at provincial levels, is important for effective prevention strategies and improvement. The aim of this analysis from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) is to investigate the disease burden of stroke and its risk factors at national and provincial levels in China from 1990 to 2019. MethodsFollowing the methodology in the GBD 2019, the incidence, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
270
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 445 publications
(324 citation statements)
references
References 37 publications
4
270
1
Order By: Relevance
“…However, there are still some limitations: (1) This is only a single-center retrospective study with a small sample size limited to Chinese patients, and some results may vary among different populations. Though studies have shown that the characteristics and prevalence of cerebrovascular and cardiovascular risk factors in the Asian population are similar to those of other large contemporary trials and real-world registries that also include other ethnicities [ 41 43 ], further studies involving different populations and more centers are needed to support our findings. (2) Although our model was adjusted for several covariates that might have an impact on the outcomes, there are still some possible influencing factors that have not been collected.…”
Section: Discussionsupporting
confidence: 70%
“…However, there are still some limitations: (1) This is only a single-center retrospective study with a small sample size limited to Chinese patients, and some results may vary among different populations. Though studies have shown that the characteristics and prevalence of cerebrovascular and cardiovascular risk factors in the Asian population are similar to those of other large contemporary trials and real-world registries that also include other ethnicities [ 41 43 ], further studies involving different populations and more centers are needed to support our findings. (2) Although our model was adjusted for several covariates that might have an impact on the outcomes, there are still some possible influencing factors that have not been collected.…”
Section: Discussionsupporting
confidence: 70%
“…Stroke was the third highest cause of death of China1 and the leading cause of disability-adjusted life-year (DALY) in China in 2019 2. Stroke has imposed an enormous disease burden on the healthcare system in China.…”
Section: Introductionmentioning
confidence: 99%
“…Pathophysiologically, stroke is defined as an abrupt neurological outburst caused by impaired perfusion through the blood vessels to the brain [ 5 ]. Despite the continuous efforts in the prevention and treatment of the disease, particularly for the various reperfusion therapies [ 5 ], stroke remains one of the leading causes of morbidity and mortality for people worldwide, particularly in developing countries [ 6 , 7 ]. Accumulating evidence suggests that dysglycemia, including stress-induced hyperglycemia [ 8 ], persistent hyperglycemia [ 9 ], as well as hypoglycemia [ 10 ], are all associated with poor prognosis in patients with acute stroke, which suggests the possible role of glucose fluctuation as a predictor of poor outcomes in patients with acute stroke [ 11 ].…”
Section: Introductionmentioning
confidence: 99%